2020
DOI: 10.3390/ijms21020471
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Met Receptor Level on HGF-Induced Glycolytic Reprogramming in Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is known to overexpress a variety of receptor tyrosine kinases, such as the HGF receptor Met. Like other malignancies, HNSCC involves a mutual interaction between the tumor cells and surrounding tissues and cells. We hypothesized that activation of HGF/Met signaling in HNSCC influences glucose metabolism and therefore substantially changes the tumor microenvironment. To determine the effect of HGF, we submitted three established HNSCC cell lines to mRNA sequencing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…For investigating the effects of HGF stimulation in HNSCC on PD-L1 concentration, we chose three commercially available cell lines: Detroit 562, FaDu, and SCC-9. We already used these three cell lines in a project dealing with glycolytic reprogramming upon HGF stimulation [ 28 ]. As part of this project, RNA was isolated, and mRNA sequencing was performed after stimulating the cells with 50 ng/mL HGF for 16 h. Figure 1 a shows the results of this mRNA sequencing for the levels of the mRNA of CD274, the gene coding for PD-L1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For investigating the effects of HGF stimulation in HNSCC on PD-L1 concentration, we chose three commercially available cell lines: Detroit 562, FaDu, and SCC-9. We already used these three cell lines in a project dealing with glycolytic reprogramming upon HGF stimulation [ 28 ]. As part of this project, RNA was isolated, and mRNA sequencing was performed after stimulating the cells with 50 ng/mL HGF for 16 h. Figure 1 a shows the results of this mRNA sequencing for the levels of the mRNA of CD274, the gene coding for PD-L1.…”
Section: Resultsmentioning
confidence: 99%
“…Investigations trying to determine the influence of Met on PD-L1 in other tumor diseases already found a high level of PD-L1 in Met amplified cell lines without HGF treatment [ 18 , 33 ]. In our study, we investigated the Met amplified cell line Detroit-562 [ 28 ]. It did not harbor significantly more PD-L1 mRNA or protein than the other two cell lines without HGF stimulation (see Figure 1 a,c).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, Wang et al suggested that c-MET expression in tumor cells suppresses the function of NK cells and T cells via the production of indoleamine-2,3-dioxygenase 18 . In addition, the activation of HGF/Met signaling in HNSCC increases glycolysis, which would result in the suppression of T-cell functions 19 . Thus, c-Met expression in tumor cells contributes to immune suppression through a variety of mechanisms.…”
Section: Discussionmentioning
confidence: 99%